Ketamine and xylazine combinations for short-term immobilization of wild variable flying foxes (Pteropus hypomelanus). - Abd Rahman, Sohayati; C. Mamat, Zaini; Hassan, Latiffah; Epstein, Jonathan Harris; Arshad, Siti Suri; Syed Hassan, Sharifah; Daszak, Peter (American Association of Zoo Veterinarians, 2008)
Collection of biological samples from pteropid bats requires chemical restraint of the bats to minimize risks to humans and stress to the bat. The effectiveness of an intravenous combination of ketamine and xylazine for short-term restraint of wild-caught variable ﬂying foxes (Pteropus hypomelanus) in a ﬁeld situation was evaluated. Eight adult male variable ﬂying foxes were injected intravenously with 0.1 ml of ketamine and xylaxine containing 5 mg of ketamine and 1 mg of xylazine. The mean induction time was 80 20 sec, and mean immobilization time was 26 10 min. The ketamine–xylazine combination used in this study produced effective short-term immobilization of wild variable ﬂying foxes for the collection of biological samples.